Let’s speak / Kimberley Lau Yih Long ... [et al.] - Kimberley, Lau Yih Long; Runggol, Christine Jacqueline; Rijeng, Jacqueline Susan; Michael, Tiong Hock Bing (Universiti Teknologi MARA, Kedah, 2023)
Let’s Speak is a virtual tutoring kit specifically designed to address the challenges faced by students in Sarawak, Malaysia, during the COVID-19 pandemic. With the closure of physical classrooms and the transition to online learning, one of the critical issues that emerged was the limited availability of a reliable internet connection, especially for students residing in remote villages in the outskirts of Sarawak. Additionally, unpredictable weather conditions, such as heavy rainfall, further exacerbated the problem by hindering connectivity. In response to these pressing concerns, Let's Speak was developed with the aim of creating an engaging and accessible learning environment for students, regardless of their geographical location or internet connectivity. The platform was initially created for Integrated Language Skills 1 (ELC121), focusing specifically on improving speaking skills. However, it has evolved beyond its original purpose and is now being utilized as a versatile virtual tutoring kit for blended learning lessons. Let’s Speak encompasses three primary objectives. Firstly, it aims to create an interesting learning environment that captivates students and fosters their speaking abilities by utilizing interactive and engaging tools. Secondly, Let's Speak promotes self-directed learning among students by providing a user-friendly interface and a vast range of resources. Lastly, Let's Speak serves as a valuable feedback mechanism for both instructors and students. The pilot test results have been extremely promising, with students expressing positive views about Let's Speak as a practical and useful tool for learning speaking. Given its success and potential impact, Let's Speak possesses significant commercialization potential. It can be marketed as an e-speaking textbook, a ready-made teaching aid that can revolutionize language education not only in Malaysia but also in other regions facing similar challenges. By leveraging technology to overcome the limitations of physical classrooms and poor internet connectivity, Let's Speak has created an accessible and engaging learning platform.